KOMUNIKASI RITUAL DALAM UPACARA TAWUR LABUH GENTUH DI TAMAN MAYURA KOTA MATARAM - Asmara Putra, I Nyoman Buda (Institut Hindu Dharma Denpasar, 2021)
Communication is a fundamental need in human life. By communicating, humans interact with God, fellow humans and the natural environment to establish a harmonious life. Hindus in West Nusa Tenggara carry out a tawur labuh gentuh ceremony at Mayura Park, Mataram City implementing the tri hita karana concept. In the process of implementing the tawur labuh gentuh ceremony, communication dynamics occur using symbols that need to be understood together. This study, entitled